Electrodeposition and Characterization of Composition-Graded Cdsxse(1-X) Multilayer Thin Film Structures - Baez-Aguilera, C; Baez-Aguilera, C (Elsevier Ltd, 2016)
In this study, the electrodeposition of a composition-graded stacked CdSxSe(1-x) multilayer film is a matter which is reported for the first time. The electrodeposition was carried out using CdSO4, Na2S2O3 and SeO2 as precursors in an acid solution. Previously, an exhaustive electrochemical study was carried out in order to establish the best condition for the electrodeposition of this structure. In order to confirm the feasibility of the method proposed, CdSxSe(1-x) single-layer films of different composition were electrodeposited and characterized. The electrodeposition of the composition-graded stacked layer arrangement was potentiostatically performed through successive electrodeposition steps in a unique electrolytic solution in which its Se content is gradually increases. The characterization of both, single-layer films and multilayer structure was performed using different techniques, confirming the formation of an alloy between CdS and CdSe. Furthermore, the multilayer structure composition gradually changes from pure CdS to a rich selenium CdSxSe(1-x) compound as the electrolytic solution composition increases its SeO2, forming a depth bandgap graded material. © 2016 Elsevier B.V.